Prenatal Diagnosis of Fryns Syndrome through Identification of Two Novel Splice Variants in the PIGN Gene—A Case Series - Aruna Marchetto; Susanne Leidescher; Theresia van Hoi; Niklas Hirschberger; Florian Vogel; Siegmund Köhler; Ivonne Alexandra Bedei; Roland Axt-Fliedner; Moneef Shoukier; Corinna Keil (Life, 2024)
Fryns syndrome (FS) is a multiple congenital anomaly syndrome with different multisystemic malformations. These include congenital diaphragmatic hernia, pulmonary hypoplasia, and craniofacial dysmorphic features in combination with malformations of the central nervous system such as agenesis of the corpus callosum, cerebellar hypoplasia, and enlarged ventricles. We present a non-consanguineous northern European family with two recurrent cases of FS: a boy with multiple congenital malformations who died at the age of 2.5 months and a female fetus with a complex developmental disorder with similar features in a following pregnancy. Quad whole exome analysis revealed two likely splicing-affecting disease-causing mutations in the PIGN gene: a synonymous mutation c.2619G>A, p.(Leu873=) in the last nucleotide of exon 29 and a 30 bp-deletion c.996_1023+2del (NM_176787.5) protruding into intron 12, with both mutations in trans configuration in the affected patients. Exon skipping resulting from these two variants was confirmed via RNA sequencing. Our molecular and clinical findings identified compound heterozygosity for two novel splice-affecting variants as the underlying pathomechanism for the development of FS in two patients.